Eudendrium tottoni Stechow 1932 - M. P. Oliveira 1, 16; S P. Miranda 2, *,; Es W. Mianzan 10,; Ro E. Migotto 11,; Ne B. Nascimento 2, 11; Eli Nogueira Júnior 12,; Er Quiñones 13,; Izio Scarabino 14,; Tín Schiariti 10,; Io N. Stampar 15,; Tronolone 2; , Quíria B.; et al. (Zenodo, 2016)
Eudendrium tottoni Stechow, 1932 Synonyms in the area: Eudendrium antarcticum —Broch 1948; Stepanjants 1979 [polyp]; Eudendrium ramosum —Blanco 1984a, 1994a [non Eudendrium ramosum (Linnaeus, 1758)] [polyp]. Distribution in South America: polyp—Atlantic Ocean, at 54.143°S 36.676°W in Puerto Leith, and at South Georgia Islands (Broch 1948; Stepanjants 1979; Blanco 1984a, 1994a). Habitat: polyp—from intertidal zone to 220m depth (Broch 1948; Stepanjants 1979; Blanco 1994a). : Published as part of M. P. Oliveira 1,16, S P. Miranda 2, *,, Es W. Mianzan 10,, Ro E. Migotto 11,, Ne B. Nascimento 2,11, Eli Nogueira Júnior 12,, Er Quiñones 13,, Izio Scarabino 14,, Tín Schiariti 10,, Io N. Stampar 15,, Tronolone 2, , Quíria B. & Onio C. Marques 2,11, 2016, Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters, pp. 1-256 in Zootaxa 4194 (1) on page 62, DOI: 10.11646/zootaxa.4194.1.1